Seabird interactions around offshore wind turbines in the North Sea - Repas-Goncalves, Miguel; Pina, Luis; Barton, Colin; Canario, Filipe; Catry, Paulo; Oliveira, Ricardo; Perrow, Martin; Segurado, Pedro; Tarrant, Polly; Tomé, Ricardo; May, Roel (Zenodo, 2022)
Seabirds represent a key consenting risk for offshore wind farms. The quantification of the risk that an offshore wind farm development could have on seabirds requires a suite of modelling tools which rely on the parameterisation of key inputs, such as flight heights, avoidance rates, collision rates, among others. Crucial in this context is to identify the underlying mechanisms of evasive behavioural responses by birds to wind turbines, and reveal species-, site- and state-specific factors enhancing avoidance and thereby affecting collision risk. However, the uncertainty arising from the lack of robust empirical data requires a cautious usage of these models, resulting in conservative estimates of the involved risks. The proposed study will analyse seabird interactions at the Neart na Gaoithe offshore wind farm in the North Sea, to collect empirical data and derive models for such interactions, and ultimately, to evaluate the effects of such structures on marine birdlife. The key species of focus in this Study are Northern Gannet and Black-legged Kittiwake. The seabird monitoring equipment, will be fully installed and operational before the wind farm becomes operational and, will collect data over the first two years of the wind farm operation for the scientific study. On-site observers will also provide data for the study, to validate and complement the data from the digital monitoring systems which will be installed in multiple locations across the offshore wind farm. The study will focus on macroavoidance dynamics when birds are approaching the wind farm and try to avoid it as a whole,meso avoidance dynamics, that correspond to deviations in the bird flight path to avoid individual turbines or arrays of turbines within the wind farm perimeter and, micro avoidance dynamics, when birds try to avoid individual wind turbine blades. The study will then tryto answer the following questions: 1)Does collision occur and are there empirical methods to record seabird collisions at offshore wind farms? 2)What are the ...